Disinformasi Digital dalam Perspektif Al-Qur’an: Tafsir Tematik atas Ayat-Ayat Tabayyun di Era Algoritma - Qonita Fathin Suhaila; Nazwa Nadia; Farid Adnir (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The rise of digital disinformation in algorithm-based communication ecosystems has changed the mechanisms of information production, distribution, and consumption, thereby increasing the opportunity for the spread of misleading information through the logic of virality, content personalization, and the reinforcement of cognitive biases. This condition places the concept of tabayyun in the Qur’an as a relevant epistemological framework for examining the contemporary information crisis. This study aims to analyze the concept of tabayyun in the Qur’an, trace the genealogy of misleading information from a Qur’anic perspective, identify the Qur’anic epistemological critique of the logic of algorithms and the culture of virality in the Qur’an, and explain the relevance of the verses of tabayyun in understanding the dynamics of digital disinformation. This research is a qualitative, literature-based study with a thematic interpretation (mawḍūʻī) approach to verses on tabayyun, information, lies, prejudice, and news dissemination. The results of the study indicate that the Qur’an establishes an information verification system that places source checking, fact validation, evaluation of informant credibility, and control of prejudice as prerequisites for the formation of valid knowledge. The Quran also identifies factors contributing to the emergence of misleading information, such as haste in accepting news, the dominance of prejudice, information manipulation, and the reproduction of news without adequate verification. The Quran’s critique of accepting information without evidence closely aligns with the algorithmic problem of amplifying content without regard for its validity. Thus, tabayyun is a fundamental epistemological principle that remains relevant as an analytical tool for addressing the information crisis and disinformation in the algorithmic era.